DISTRIBUSI KERUANGAN DAERAH TERKENA BENCANA KEKERINGAN DAN KESIAPSIAGAAN RUMAH TANGGA DALAM MENGHADAPI BENCANA KEKERINGAN DI KECAMATAN BRINGIN KABUPATEN SEMARANG - Reynaldi, Widdy; Hardati, Puji; Parman, Satyanta (Geo-Image, 2017)
The aim research to know spatial distribution villages affected drought, characteristics disaster households drought, and household preparedness drought in district Bringin. Research method is quantitative descriptive. Technique data collection with the documentation, questionaire, interview, observation. Sampling techniques using sampling area to find sample region examined villages with level regions drought and technique purposive random sampling specified village samples and sampling proportional to number each region samples taken together. Result spatial distribution villages affected drought consists three categories low, medium and high. Low class village named Truko, medium categories named Wiru, high categories named Rembes. Household characteristics drought in village of Truko classified well to support drought preparedness, Wiru Village classified as a household characteristics enough to support drought preparedness, while villages classified as Rembes not good. Level of village preparedness. Preparedness household in Truko including ready, Villages Wiru quite ready, while Villages Rembes not ready.